The Missing Piece: Domestic Civil Society Access to Human Rights Treaty Bodies - Wong, Vincent (2019)
Since 2009, the United Nations has been engaged in a process of ‘strengthening’ the human rights treaty body system which monitors the implementation of the core international human rights treaties. The number of human rights treaty bodies has, over time, expanded to ten, with each treaty body independently tasked with monitoring an increasing number of States Parties’ compliance with human rights treaties and optional protocols. This proliferation has in turn precipitated the need for a process to improve the overall functioning of the system.While significant attention has been dedicated in the treaty body strengthening process to the issue of States Parties’ under-reporting and capacity deficits, comparatively little attention has been directed towards accessibility issues, capacity building, and technical assistance for domestic civil society organizations (CSOs) - groups whose informed and active participation are essential to the proper functioning of the entirety of the treaty body system. In light of this lack of attention, an ecosystem of intermediary non-government organizations (NGOs) has emerged organically to provide much needed capacity building, advisory services, and technical assistance to domestic CSOs looking to engage with treaty bodies. However, the ad hoc nature in which these intermediary NGOs have emerged and the lack of formalized institutional relationships with treaty bodies has resulted in a number of systemic issues that desperately need to be addressed in the treaty body strengthening process.This paper will discuss the ongoing process of treaty body strengthening, current services provided by intermediary NGOs to assist domestic CSOs in engaging with human rights treaty bodies (as well as the Universal Periodic Review), gaps within the current framework, and recommendations to improve access for domestic CSOs within the current treaty body strengthening process.
Keywords: Vincent Wong